Unsaturated soils: research and applications : Volume 1 - Jommi, Cristina; D'Onza, Francesca; Mancuso, Claudio (Springer Berlin Heidelberg, 2012)
These volumes contain the contributions to the Second European Conference on Unsaturated Soils, E-UNSAT 2012, held in Napoli, Italy, in June 2012. The event is the second of a series of European conferences, and follows the first successful one, organised in Durham, UK, in 2008. The conference series is supported by Technical Committee 106 of the International Society of Soil Mechanics and Geotechnical Engineering on Unsaturated Soils. The published contributions were selected after a careful peer-review process. A collection of more than one hundred papers is included, addressing the three thematic areas experimental, including advances in testing techniques and soil behaviour, modelling, covering theoretical and constitutive issues together with numerical and physical modelling, and engineering, focusing on approaches, case histories and geo-environmental themes. The areas of application of the papers embrace most of the geotechnical problems related to unsaturated soils. Increasing interest in geo-environmental problems, including chemical coupling, marks new perspectives in unsaturated soil mechanics. This book will provide a valuable up-to-date reference across the subject for both researchers and practitioners.